Learning Pyramid Models To Improve Early Childhood Science Skills - Gatot, Masitowati (Archives of Business Research, 2018)
This study was to produce a valid and effective models to improve science process skills. Validity of learning gained through expert validity and limited testing (one to one and small group). Learning effectiveness is measured through a simple experiment using 9 (nine) step model of Borg, Gall and Gall. The aims of this methodology of research is to find how a teacher can implement teacher’s guidance book study model pyramide based method. The result shows during pre test: 56,3% teachers teach in accordance with given criteria while 48,3% they don’t. On the contrary, based on post test data: 93,3% teachers teach in line with the criteria, while 6,25% they don’t. Meanwhile, the results of Students study in overall show there is an increase when students are conducting pre test and post test. The conclusions of this study are that the guidebooks produced and used, show improvement of teacher performance and improvement of basic science skills of children.